Development of a decision-making system for transportation in remote inter-island area - Quoc Hai, Dang; Thai Hoang, Pham; Hoang Thao, Doan Thi; Gia Huy, Dinh; Thanh Tien, Le (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2024)
The transportation of goods and people between islands poses distinctive logistical hurdles due to the geographical remoteness and varied infrastructure prevalent in island settings. This study introduces a theoretical framework designed to improve the efficiency of selecting and routing hub islands in an inter-island logistics network by utilizing the hub-and-spoke model. The process of identifying potential hub islands involves an initial assessment of several criteria, encompassing geographical, economic, and equipment-related factors. The utilization of Floyd’s algorithm was employed in the computation of the shortest distance matrices between islands, with consideration given to the avoidance of ship collisions. The identification of the required hubs is determined by employing a location set covering model, which includes a constraint on the maximum distance for service provision. The p-Median model was employed to ascertain the most efficient hub locations to minimize transportation expenses. The framework provides a quantitative approach to designing efficient logistics networks for inter-island transportation. It considers important factors, such as shipping routes, hub locations, and collision avoidance. The utilization of this methodology holds promise for augmenting connectivity and streamlining resource accessibility in geographically isolated island areas with limited infrastructure.